Colour analysis of organic synthetic dye coating paint films consisting 4-hydroxycoumarin derivatives after exposed to UV-A. (10th April 2019) - Manah, N S A; Sulaiman, L; Azman, N L S M; Abidin, Z H Z; Tajuddin, H A; Halim, N A
Abstract: This work investigates the visible optical stability of coating paint film consisting organic synthetic dye, 4-hydroxycoumarin derivatives to the exposure to ultraviolet A (UV-A) light. An azo dye was synthesized by coupling diazonium salt of aniline derivative (obtained by diazonation of 4-chloroaniline in presence of sodium nitrite and hydrochloric acid) with 4-hydroxycoumarin in the presence of sodium hydroxide. The azo dye was mixed with xylene before using it as a pigment in the coating composition. The mixture of poly(methyl methacrylate) (PMMA) and acrylic polyol was used as the coating binder. The synthesized dye and binder were then mixed at specific ratio to form a complete coating solution. Two coating solutions with PMMA having different molecular weights (Mw: 350, 000 gmol −1 and Mw: 996, 000 gmol −1 ) were used in this study. Each of them was labelled as 350 K and 996 K indicating its molecular weight. Both mixtures were applied as coating paint films on glass substrates were exposed to UV-A for fast photo-degradation process. The visible optical stability of the coating paint films was measured and recorded at an interval of eight-hours exposure for 35 days using the Commission Internationale de l'Eclairage (CIE) L*a*b* colour coordinate system. The obtained datas were analysed using standard deviation (STD). In this study, both coating samples showed low standard deviation for hue angle, namely 0.206 for 996 K and 0.258 for 350 K which indicates a high colour stability. However, the 350 K possesses a smaller colour difference (ΔE) of 0.798 compared to 1.418 for 996 K.